CREATING A FAVORABLE INVESTMENT ENVIRONMENT TO ATTRACT FOREIGN INVESTMENTS INTO ECONOMIC NETWORKS IN UZBEKISTAN - Ahmedova Feruza Khakimovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides analytical information on creating a favorable investment environment for attracting foreign investment in the sectors of the economy of Uzbekistan.